The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1600-051x.2007.01118.x
|View full text |Cite
|
Sign up to set email alerts
|

Reported methodological quality of split‐mouth studies

Abstract: Despite some progress in statistical analysis, if the reporting of studies represents the actual methodology of the trial, this review has identified important aspects of split-mouth study design and analysis that would benefit from development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
75
2
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 19 publications
6
75
2
5
Order By: Relevance
“…Quando o paciente serve como seu próprio controle, aumenta a eficiência estatística e diminui a quantidade de pacientes necessários para o estudo (17,21).…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Quando o paciente serve como seu próprio controle, aumenta a eficiência estatística e diminui a quantidade de pacientes necessários para o estudo (17,21).…”
Section: Discussionunclassified
“…Na pesquisa de levantamento das metodologias aplicadas nesse tipo de estudo, desenvolvida por LESAFFRE et al (17), foi detectada a variação contralateral como a metodologia mais popular utilizada nas pesquisas clínicas.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Few studies have examined the use of statistical methods in dental research papers. Yang et al (2001) estimated the availability of statistical information in paediatric dentistry, and Lesaffre et al (2007) concluded that the split-mouth study design and analysis would benefit from improvements in the use of statistical methods. Vähänikkilä et al (2009Vähänikkilä et al ( , 2012 showed that the use of multivariable or computational methods in dental journals from 1996 to 2006 did not increase.…”
mentioning
confidence: 99%